Pengaruh Profitabilitas, Kualitas Audit dan Transformasi Digital Terhadap Nilai Perusahaan dengan Manajemen Laba Sebagai Variabel Moderasi: Studi Perusahaan Konstruksi pada Bei Periode 2019-2023 - Putri Zahra Afiifah; Suratno; JMV Mulyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the influence of profitability, audit quality and digital transformation on company value, as well as the moderating role of earnings management in construction companies in Indonesia during the 2019-2023 period. By using secondary data in the form of annual reports of companies listed on the Indonesia Stock Exchange, this research applies a multiple linear regression model with interactions (MRA). The research results show that profitability (measured by ROA) and digital transformation have a significant positive effect on company value, with B coefficients of 0.263 (p-value = 0.000) and 0.116 (p-value = 0.026), respectively. On the other hand, audit quality has no significant effect (B = -0.006, p-value = 0.933). In addition, earnings management moderates the influence of audit quality and digital transformation on firm value, but does not moderate the relationship between profitability and firm value. These findings emphasize the importance of profitability and digital transformation in increasing company value in the construction sector, as well as the role of earnings management in strengthening the influence of several of these factors. This research contributes to understanding the factors that influence company value in the Indonesian construction industry.